2014
DOI: 10.1038/ncomms4635
|View full text |Cite
|
Sign up to set email alerts
|

Timescales for detecting a significant acceleration in sea level rise

Abstract: There is observational evidence that global sea level is rising and there is concern that the rate of rise will increase, significantly threatening coastal communities. However, considerable debate remains as to whether the rate of sea level rise is currently increasing and, if so, by how much. Here we provide new insights into sea level accelerations by applying the main methods that have been used previously to search for accelerations in historical data, to identify the timings (with uncertainties) at which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 47 publications
4
144
0
Order By: Relevance
“…The current view based on observations from the recent past and future projections by coupled GCMs is a long-term trend of rising sea level with natural variations superimposed on this general trend on a range of time scales and due to a number of physical drivers including atmospheric pressure and wind, and large-scale steric variations . This variability obscures the detection of regional climate trends (Haigh et al 2014) both in observations and scenario simulations. Variations in the time-average sea level can be driven by a number of processes.…”
Section: Time-mean Sea Level Changementioning
confidence: 99%
“…The current view based on observations from the recent past and future projections by coupled GCMs is a long-term trend of rising sea level with natural variations superimposed on this general trend on a range of time scales and due to a number of physical drivers including atmospheric pressure and wind, and large-scale steric variations . This variability obscures the detection of regional climate trends (Haigh et al 2014) both in observations and scenario simulations. Variations in the time-average sea level can be driven by a number of processes.…”
Section: Time-mean Sea Level Changementioning
confidence: 99%
“…It is unclear, however, to what extent this higher rate represents natural variability rather than a sustained increase owing to global warming. A detailed study of possible accelerating sea level along the Norwegian coast is not made here, but we note that the climate change signal from increasing greenhouse gases needs time to emerge from natural climate variability, and the sea-level rise observed over recent periods is not significantly larger than rates observed at other times within the past century [36][37][38][39]. This is demonstrated in Figure 4, which shows how the estimated rates vary for a 30-year moving window shifted in steps of 1 year from 1960 to 1986.…”
Section: Sea-level Rates Along the Norwegian Coastmentioning
confidence: 99%
“…Haigh et al [27] demonstrated the difficulty of estimating accelerations from local tide-gauge observations, the necessity for long time series (Douglas [28] argued that almost 50 years was required), and the importance of removing unforced and naturally forced variability.…”
Section: Historical Sea Levelmentioning
confidence: 99%